2017
DOI: 10.36876/smjbb.1006
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis and InterComparison of Solar UVB and Global Radiation for Athalassa and Larnaca, Cyprus

Abstract: A statistical analysis and inter-comparison of the broadband ultraviolet-B (UVB) radiation at two sites in Cyprus representing two different climate regimes of the island (Athalassa-inland plain vs Larnaca-coastal location) covering the period January 2013-December 2015 is presented. Mean annual and mean monthly daily totals of the UVB irradiation and their frequency distribution at both sites are computed and discussed. Daily maximum of hourly average irradiance values occur in July, 2.09 W m -2 , and minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…As previously indicated by other authors (e.g., Bell et al, 2006;Martynov et al, 2010;MacKay, 2012), sufficient radiation data (both shortwave and longwave) are not generally available from routine meteorological measurements, and this is also the case for meteorological station M, where only UVB radiation was measured. A number of studies provide correlations among UVA, UVB, total UV, or global solar radiation (G) (Kudish and Evseev, 2000;Kudish et al, 2005;Podstawczynska, 2009;Pokhrel and Bhattarai, 2012;Pashiardis et al, 2017) and show that significant variability occurs in the UV/G ratio between sites, which is mainly due to local atmospheric conditions. Podstawczynska (2009) indicated that air turbidity and cloudiness are the two main factors that determine the variability of daily solar energy transmission through the atmosphere.…”
Section: Shortwave Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously indicated by other authors (e.g., Bell et al, 2006;Martynov et al, 2010;MacKay, 2012), sufficient radiation data (both shortwave and longwave) are not generally available from routine meteorological measurements, and this is also the case for meteorological station M, where only UVB radiation was measured. A number of studies provide correlations among UVA, UVB, total UV, or global solar radiation (G) (Kudish and Evseev, 2000;Kudish et al, 2005;Podstawczynska, 2009;Pokhrel and Bhattarai, 2012;Pashiardis et al, 2017) and show that significant variability occurs in the UV/G ratio between sites, which is mainly due to local atmospheric conditions. Podstawczynska (2009) indicated that air turbidity and cloudiness are the two main factors that determine the variability of daily solar energy transmission through the atmosphere.…”
Section: Shortwave Radiationmentioning
confidence: 99%
“…Podstawczynska (2009) indicated that air turbidity and cloudiness are the two main factors that determine the variability of daily solar energy transmission through the atmosphere. Pashiardis et al (2017) found that the UV/G ratio increases with solar elevation and that the presence of clouds reduces the UV component less than the global solar radiation due to the strong absorption of water in the near infrared spectrum. Winslow et al (2001) proposed a model for estimating the total daily solar irradiance from daily precipitation and minimum and maximum temperatures, along with latitude, elevation, and mean annual temperature.…”
Section: Shortwave Radiationmentioning
confidence: 99%